Slow Storytelling and hybridity: Re-staging community storytelling as a tool for co-thinking. Issue 1 (1st August 2021) - Wilson, Michael
Since the early 2000s social media has transformed the internet into a site for the exchange of stories through the mass democratization of publishing. And yet, new forms of digital and online storytelling have at the same time compromised one of the core functions of storytelling, namely its social aspect, the ability to build community when two or more people share stories in the same space, at the same time, breathing the same air. Somewhat ironically the advent of social media may have broadened the audience for any one person's storytelling, whilst diminishing the social intimacy of the storytelling experience. As part of its research work into storytelling as a means of engaging people in the public debate around environment, the Storytelling Academy at Loughborough University has been developing new forms and processes of digital storytelling to promote wider engagement and dissemination of environmentally driven personal stories. 'The Reasons', first staged in Cambridgeshire in 2016, was an attempt to create a live, community social event that provided a public forum for storytelling as a way of debating issues around drought and water governance in the Fens. Inspired by a re-staging of La Rasgioni in Sardinia in 2015, a traditional form of conflict resolution, whereby a 'mock' court provides the means for the community to publicly tell its stories to each other, 'The Reasons' was co-designed for the Fenland context and was performed twice in 2016. It was then further adapted for use in the Korogocho slum in Nairobi for an event to discuss the issue of waste management with members of the local community, as part of an initiative with UN Live. 'The Reasons' is an attempt to bring together the advantages of digital storytelling as a reflective process with the social intimacy of the live storytelling event. The result is a new form of hybrid storytelling that seeks to build community and establish co-thinking processes to build resilience to environmental change. This article reflects critically upon the development and evolution of this work over the past five years.